Internet Addiction: a prevention action-research intervention (Epidemiology, Biostatistics, and Public Health, 2022)
The aim of this paper was to present an action-research intervention for the prevention of Internet addiction (IA) in schools. Applying a pre-experimental research design model, a total of 90 young subjects (45 males and 45 females) were treated using a peer education programme. The Internet Addiction Test was used as a screening tool pre- and post-treatment and analysed using a paired t-test. The results showed a significant positive difference in the post-treatment values for both males and females. This research highlights the link between IA and cultural and social aspects of the disease in addition to discussing the difficulties of IA prevention.
Keywords: Internet Addiction; New Addictions; Prevention; peer education; IAT